Analysis of the Benefits of Biopore Infiltration Holes in Pengabdian Park Tiyuh Mulya Jaya, Tulang Bawang Barat Regency, Lampung - Listiana, Ika; Kuswanto, Eko; Sari Pratama, Anisa Oktina (INSTITUT AGAMA ISLAM NEGERI AMBON, 2025)
Environmental problems caused by the decrease in green open spaces (RTH) and the increasing land conversion have disrupted the water infiltration system, leading to flooding during the rainy season and droughts during the dry season. One solution that can be implemented is the use of biopore infiltration holes (LRB) as a groundwater conservation method. This study aims to analyze the effectiveness of LRB in reducing rainwater runoff at Taman Pengabdian Tiyuh Mulya Jaya, Tulang Bawang Barat Regency. The research method used is quantitative descriptive with data collection techniques through observation, documentation, and rainfall intensity measurement. The research site covers an area of ±2100 m², with 21 LRBs applied. Data analysis was carried out to determine the optimal placement of LRBs, the ideal number of infiltration holes, and the volume of water absorbed. The results show that LRBs are effective in increasing water infiltration into the ground, reducing puddles, and maintaining groundwater availability. In this study, the total rainwater storage volume obtained was approximately ±37745.72 L, the application of LRBs has contributed to addressing rainwater runoff issues and supporting environmental conservation efforts. Therefore, the effectiveness in handling runoff water reached 43%. Keywords: Biopore Infiltration Holes, Water Availability, Runoff Water Management